Optimal weak estimates for Riesz potentials - Huang, Liang; Tang, Hanli (Comptes Rendus. Mathématique)
In this note we prove a sharp reverse weak estimate for Riesz potentials \[ \Vert I_{s}(f)\Vert _{L^{\frac{n}{n-s},\infty }}\ge \gamma _sv_{n}^{\frac{n-s}{n}}\Vert f\Vert _{L^1}~\text{for}~0